Diagnostic Yield of Timing Blood Culture Collection Relative to Fever. Issue 8 (August 2016) - Kee, Penny Pei Lee; Chinnappan, Maidhili; Nair, Ajit; Yeak, Daryl; Chen, Annie; Starr, Mike; Daley, Andrew J.; Cheng, Allen C.; Burgner, David
Abstract : Background: Conventional practice involves obtaining a blood culture during or immediately after a fever to increase diagnostic yield. There are no data to support this practice in children. Methods: Retrospective single-center case-control study of children (0–18 years) who had blood cultures performed as part of routine care. Cases had an a priori defined pathogen isolated from blood culture (n = 410) and were age-matched with contemporaneous controls with a sterile blood culture (n = 410). The predictive value of fever (before and after blood culture), C-reactive protein and hematologic indices were analyzed by multivariate regression and area under the receiver operating characteristic curves (AUCs) in neonatal, general pediatric and pediatric oncology patients. Results: One thousand one hundred seventy-two (6.7%) of 17, 607 blood cultures were positive, of which 410 (35%) cultured pathogen(s). Three hundred and twenty four (79%) cases and 275 (67.1%) controls had a fever (≥37.5°C) during the 12 hours pre- or post-collection. Fever 2–6 hours before a blood culture was neither sensitive nor specific for predicting bacteremia in neonatal or pediatric patients and marginally predictive in oncology patients (AUC 0.59–0.63). Cultures obtained 2–6 hours before fever were nonpredictive in neonates (AUC 0.56–0.59), marginally predictive in pediatric patients (AUC 0.64–0.67) and moderately predictive in oncology patients (AUC 0.70). C-reactive protein was marginally predictive in neonates (AUC 0.60). Hematologic indices were nonpredictive in all groups. Conclusions: Fever before obtaining blood culture was neither sensitive nor specific for culture positivity; timing of pediatric blood cultures relative to fever is unimportant. Bacteremia precedes a fever, but this is of limited clinical applicability. Abstract : Supplemental Digital Content is available in the text.